Nonmuscle Myosin Heavy Chain ⅡA-Mediated Exosome Release via Regulation of the Rho-Associated Kinase 1/Myosin Light Chains/Actin Pathway - Lv, Yanni; Chen, Jin; Hu, Jinfang; Qian, Yisong; Kong, Ying; Fu, Longsheng (Frontiers in Pharmacology, 2020)
Nonmuscle myosin ⅡA, a kind of ATP-dependent molecular motor, binds to actin to form the molecular motors of a cell. We now found that the intervention of NMMHC ⅡA could affecte the release of exosome in microglial cells stimulated by LPS. LPS could enhance the exosome release via increasing exosome concentration, and elevating CD9, CD81 protein positive labeled rate. Added with myosin-inhibitor blebbisatin could downregulate the exosome concentration, recede CD9 and CD81 exosome surface protein expression compared with that in the LPS group. To further determine the exact subtype of myosin Ⅱ, transfected with siRNA of MYH9, MYH10, and MYH11 into microglial cells respectively. The data showed that only transfecting of siRNA-MYH9 could decrease the exosome concentration, and weaken CD9, CD81 protein positive staning rate compared with that in the LPS group. Western blot and immunofluorescence indicated that NMMHC ⅡA might trigger the ROCK1/MLC/actin signaling pathway of microglial cells under the stimulation of LPS. The potential mechanism of the release of exosome might be regulated through the NMMHC ⅡA/ROCK1/MLC/actin signaling pathway. NMMHC ⅡA might be the potential target required for exosome release.